CONSUMO HÍDRICO DE CRAVINA SUBMETIDA A DIFERENTES ESTRATÉGIAS DE IRRIGAÇÃO E TAMANHOS DE VASO - Schwab, Natalia Teixeira; Peiter, Marcia Xavier; Bellé, Rogerio Antônio; Backes, Fernanda Alice Antonello Londero; Robaina, Adroaldo Dias; Ferraz, Rafael Camargo (IRRIGA, 2013)
1 RESUMO O objetivo da pesquisa foi avaliar o consumo hídrico e o desenvolvimento de hastes florais de cravina (Dianthus hybrida ‘Melody’), submetida a diferentes estratégias de irrigação e tamanhos de vaso durante um ciclo de cultivo. O experimento foi conduzido em casa de vegetação do Departamento de Fitotecnia da Universidade Federal de Santa Maria, em esquema bifatorial (2x4) sendo os tratamentos utilizados dois tamanhos de vaso e quatro estratégias de irrigação, com cinco repetições cada. Ao final do ciclo de cultivo foram avaliados: altura das hastes; número de botões florais; número de gemas vegetativas por haste; número de ramificações por haste; diâmetro da haste; fitomassa de matéria fresca e fitomassa de matéria seca da parte aérea, e ainda determinado o consumo hídrico ao longo do ciclo. Os resultados demonstraram um incremento no consumo de água no decorrer do período de cultivo, porém os parâmetros de produtividade avaliados não sofreram interferência dos tratamentos. Palavras-chaves: Dianthus hybrida ‘Melody’, balanço hídrico, floricultura SCHWAB, N. T.; PEITER, M. X.; BELLÉ, R. A.; BACKES, F. A. A. L.; ROBAINA, A. D.; FERRAZ, R. C. WATER CONSUMPTION OF DIANTHUS MELODY UNDER DIFFERENT IRRIGATION STRATEGIES AND POT SIZES 2 ABSTRACT The aim of this research was to evaluate Dianthus Melody (Dianthus hybrida ‘Melody’) water consumption and stalk growth when submitted to different irrigation strategies and pot sizes for one crop cycle. Conducted in a greenhouse at the department of phytotechny, Universidade Federal de Santa Maria, Santa Maria, Rio Grande do Sul, Brazil, the experiment was designed as a 2x4 factorial arrangement with two pot sizes and four irrigation strategies per treatment with five replications each. At the end of the growth cycle stem height, number of buds, number of nodes per stem, number of branches per stem, stem diameter as well as the fresh and the aboveground dry stem phytomasses were evaluated and also was determined the water consumption over the cycle. The results showed an increase in water consumption during the growth stage however treatments had no effect on the evaluated productivity parameters. Keywords: Dianthus hybrida ‘Melody’, water balance, flower production lcx P split-plot design with four replications. The plots corresponded to four different concentrations of salts in the drip irrigation water (0.5, 2.2, 3.6 and 5.0 dS m-1), and the subplots consisted of four bovine biofertilizer ratios, representing 0, 15, 30 and 45% of the applied volume. The experiment evaluated the effects (of the controlled variables) on gas exchanges and productivity. The salinity of the irrigation water reduced cowpea gas exchanges (stomatal conductance, photosynthesis and internal CO2 concentration) and cowpea productivity. The leaf application of bovine biofertilizer had positive influence on the values of transpiration, grain weight and productivity of the cowpea culture under salt stress. KEYWORDS: Vigna unguiculata L. Salinization. Organic inputs.